Influence of the wollastonite and glass fibers on geopolymer composites workability and mechanical properties. (10th October 2020) - Archez, J.; Texier-Mandoki, N.; Bourbon, X.; Caron, J.F.; Rossignol, S.
Graphical abstract: Highlights: Geopolymer composites based on wollastonite and glass fibers were synthetized. Influence of the MK and additives on viscosity and working properties was studied. The wollastonite ensures a better dissolution of the metakaolin. The glass fibers act as an anchoring site during the geopolymerization reaction. The aluminum amount enables to monitor the viscosity and compressive strength. Abstract: This work aims to synthetize geopolymer composites and study the influence of the aluminum concentration, wollastonite and glass fibers on the properties of the fresh and hardened material. To this end, different metakaolin, wollastonite and glass fibers contents were used to synthesize geopolymer composites. The effect of reinforcement elements on the geopolymerization reaction has then been studied with FTIR spectroscopy and thermal analysis (DTA-TGA). Moreover, the viscosity and the setting time of the reactive mixture, as well as the compressive strength of the hardened material, have been measured for the different compositions. The results showed that the nature of the reinforcement added induces different polycondensation reactions. The wollastonite improves the viscosity and the mechanical properties by ensuring a better dissolution of the metakaolin, whereas the glass fibers act as an anchoring site during the geopolymerization reaction, leading to a ductile failure of the material. Finally, the aluminum content enables to monitor the viscosity and setting time of the reactive mixture and has a significant influence on the microstructure and the compressive strength. Thus, the initial formulation of the geopolymer composites allows controlling the properties of the fresh and hardened geopolymer composites.